ANALYSIS OF ANTIOXIDANT ACTIVITY, TOTAL PHENOLIC CONTENT AND TOTAL FLAVONOID CONTENT OF LANTANA CAMARA LEAVES AND FLOWERS - Anand, Jigisha; Chaudhary, Shanu; Rai, Nishant (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study aims at screening phytochemicals present in Lantana camara leaves and flower extracts. Methods: Methanolic extracts of leaves and flower of L. camara were prepared by the solvent extraction method. The preliminary qualitative photochemical analysis of leaves and flower extract was done following standard procedures. For quantitative phytochemical screening, total phenolic content (TPC), total flavonoid content (TFC), and free radical scavenging activity of L. camara was estimated. Results: The preliminary qualitative analysis showed the presence of flavonoids, phenols, terpenoids, anthocyanins, carbohydrates, and proteins in the methanolic extracts of Lantana leaves and flower, while saponins, glycosides, and alkaloids were not detected in both the extracts. Quantitative assays were done for determination of TPC, TFC, and free radical scavenging activity of L. camara. The methanolic extract of Lantana flowers depicted highest TFC (15.76Â±0.005 mg of hydrated catechin equivalent/ml of sample) and TPC (17Â±0.005 mg of Gallic acid equivalents equivalent/ml of sample), while both leaves and flower extracts revealed extortionately high 2, 2-diphenyl-1-picrylhydrazyl free radical scavenging activity. Conclusion: The present work depicted that L. camara leaves and flowers are rich in antioxidant activity and have a promising application as nutraceuticals for herbal drug formulations.